Gold(III) Chloride-Mediated Transformation of Furfural to the trans-N,N-4,5-Diaminocyclopent-2-enones in the Presence of Anilines - Marina A. Tzani; Ioannis N. Lykakis (Chemistry, 2023)
We investigated the efficient approach of a series of trans-N,N-4,5-substituted-diaminocyclopent-2-enones (trans-DACPs) from furfural and anilines mediated by Gold(III) chloride (HAuCl4). The present protocol required a low amount of the catalysts, 1.5 mol%, open air conditions, the absence of any additives, and short reaction times. The desired trans-DACPs were isolated in good to high yields. The protocol was also applied to secondary amines, leading to the corresponding 4,5-diamino-cyclopent-2-enones in good yields. To the best of our knowledge, this is the first gold-mediated paradigm as an efficient catalyst for the formation of the cyclopentenones core-bearing C-N bonds under mild reaction conditions.